INHIBITION ACTIVITY ASSESSMENT OF BIOSYNTHESIZED OF CUNPS BY AN ECO-FRIENDLY TECHNIQUE USING PLANT EXTRACTS AGAINST Staphylococcus aureus: INHIBITION ACTIVITY ASSESSMENT OF BIOSYNTHESIZED OF CUNPS BY AN ECO-FRIENDLY TECHNIQUE USING PLANT EXTRACTS AGAINST Staphylococcus aureus (Iraqi Journal of Market Research and Consumer Protection, 2026)
The study investigated the Minimum Inhibition Concentration (MIC) of CuNPs biosynthesis using aqueous Myrtus communis and Nerium oleander leaves extracts against Staphylococcus aureus bacteria isolated from Al-Madaen Public Hospital in Baghdad-Iraq. Ten concentrations (50.0 to 0.09) mg/ml of CuNPs were prepared to determine MIC values for each extract concentration against S. aureus bacteria. Various techniques were used to characterize CuNPs, and UV-visible light was used to screen the surface plasmon resonance (SPR) for CuNPs in scope from 200 to 600 nm. The Cu Fourier transform infrared spectroscopy (FTIR) and atomic force microscopy (AFM) revealed the nanoparticle's size and surface feature. A scanning electron microscope (SEM) was used to determine nanoparticle crystalline morphology and size. The results revealed that CuNPs of M. communis, MIC values varied from 0.09 mg/ml in well 10 of samples 1 and 2 to 0.3 mg/ml in well 8 of sample 4, whereas in the case of CuNPs of N. oleander, the MIC values were found to range from 0.09 mg/ml in well 10 of sample 2 to 0.7 mg/ml in well 7 of sample 1. In the case of mixed CuNPs, prepared from extracts of both plants, the values varied from 0.3 mg/ml in well 8 of sample 4 to 3.1 mg/ml in well 5 of sample 1. However, regarding M. communis alcoholic extract, MIC values ranged from 0.09 mg/ml in well 10 of samples 2 and 4 to 0.1 mg/ml in well 9 of samples 1 and 3. For N. oleander alcoholic extract, MIC values ranged from a minimum rate of 0.09 mg/ml to a maximum rate of 3.0 mg/ml in well 10 of sample 4 and in well 5 of sample, respectively. Finally, the MIC values of the mixed alcoholic extract of M. Commines and N. Oleander varied from 0.3 mg/ml in well 8 of sample 2 to 0.7 mg/ml in well 7 for samples 1, 3, and 4.